Dynamic ice actions in the revision of ISO 19906 - Hendrikse, H. (author) (2019)
The second edition of the ISO19906 design standard contains changes in the informative appendix concerning dynamic ice actions. Challenges in application of the previous approach and advances in understanding of the dynamic ice-structure interaction process were the main motivation for the revision. The new guideline provides relevant information for determining dynamic ice actions, but does not yet give a complete simplified design method. In this paper, the changes made in section A.8.2.6.1 covering dynamic ice actions on vertical and near vertical structures are discussed and remaining knowledge gaps are defined. Changes in the sections dealing with sloping structures and fatigue analysis were not made in the revision of ISO19906 and are therefore not considered. An important omission is identified related to the peak loads in intermittent crushing, which are potentially underestimated based on the new description. The main knowledge gap is found to be the definition of the ice drift speeds for which a specific mode of ice-induced vibrations may develop, e.g. intermittent crushing, frequency lock-in or continuous brittle crushing. These drift speeds depend on structural and ice properties. An estimation formula does not exist, hindering straightforward application of the ice load time traces as suggested in the standard. Offshore Engineering